Pengaruh Salinitas dan Kondisi Fertilisasi terhadap Persentase Larva Normal pada Kerang Bakau Polymesoda erosa Solander (1786) - Ricky Gimin (Universitas Gadjah Mada, 2006)
The mangrove clam (Polymesoda erosa) is edible bivalve and one of potential candidate for aquaculture. Availability of its hatchery technique is important for development of its aquaculture. The objective of this study was to determine the optimum salinity and fertilization factors for the production of normal larvae. Fertilized eggs at density of 10 eggs/ml were incubated under seven salinities, i.e., 0, 5, 10, 15, 20, 25 and 30 ppt at room temperature (26±1°C). The highest percentage of 48 hr normal D-larvae occurred at 20 ppt. The percentage dropped significantly if salinity was below 10 ppt or more than 25 ppt. In other experiments to develop fertilization protocols for this species, the effects of spermatozoa-to-ovocyte ratio, age of gametes, and stocking density of eggs were assessed individually to determine the optimum ratio, age and density for the highest percentage of normal D-larvae. Ten sperms-to-egg ratios, i.e., 5, 10, 50, 102, 5x102, 103, 5x103, 104, 5x104 and 105 at density of 10 eggs/ml, were tested. The highest percentage of normal D-larvae occurred within the range of 5x102 to 5x103 sperms per egg. Significantly low percentages were obtained at treatments below 100 or more than 104 sperms per egg. In the experiment of gamete age, sperms and eggs were mixed for fertilization at different times, i.e., 30 minutes, 45 minutes, 60 minutes, 120 minutes and 180 minutes, after spawning. Freshly spawned sperms and eggs of less than 60 minutes gave the best percentage. When the fertilized eggs were incubated at different densities, i.e., 10, 20, 30, 40, 50, 100 and 200 eggs/ml, the densities up to 50 eggs/ml gave maximum results.